“El gigantesco sacrificio a los dioses oscuros”: las visiones de Slavoj Žižek y Paul Celan sobre el mal, la oscuridad y un dios en fuga en las repercusiones de la Shoah - Bomholt, Marius Christian (Revista de Filología Románica, 2017)
the present paper establishes a dialogue between Paul Celan’s poetry and Slavoj Žižek contemporary thought, centered on the Shoah and its repercussions as its focal point. By means of the analysis of three aspects in particular –the notion of evil, the sense of darkness and the idea of an absconding God– it also approaches questions of the poetic representability of the Shoah and the aesthetic accessibility of Celan’s poetry, which eventually leads to a slightly broader conclusion on the role and importance of aestheticization of trauma, in the lacanian sense, in general.